“IS THE LABOUR RELATION OF THE CIVIL SERVANT AN ADMINISTRATIVE CONTRACT?” - LIANA-TEODORA PASCARIU (Challenges of the Knowledge Society, 2011)
Nowadays, public institutions have contractual employees, hired on the basis of the Labour Code, and public servants, appointed on the basis of the Civil Service Statute. If the labour relation of the public servant is not qualified as a labour contract, what is its juridical character? This paper tries to demonstrate that the civil servant develops labour relations under different circumstances, i.e. on the basis of an administrative contract.